Reciprocal cross effect over seasons on agronomic and yield traits in waxy corn under tropical savanna - MATTANA SAWANGHA; ABIL DERMAIL; SOMPONG CHANKAEW; SAKUNKAN SIMLA; KAMOL LERTRAT; KHUNDEJ SURIHARN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sawangha M, Dermail A, Chankaew S, Simla S, Lertrat K, Suriharn K. 2023. Reciprocal cross effect over seasons on agronomic and yield traits in waxy corn under tropical savanna. Biodiversitas 24: 4120-4125. The exponentially increasing number of hybrids per additional inbred lines results in a tremendous workload in crop hybrid breeding. The question arises if reciprocal crosses could be excluded in waxy corn hybrids to reduce the workload by up to 50%. In this study, we aimed to assess the importance of reciprocal cross effects for yields, yield components, and agronomic traits of sweet-waxy corn F1hybrids and to validate the stability of those effects over seasons. Five parental lines, comprised of one sweet corn inbred line and four waxy corn inbred lines, were mated through a top cross scheme to generate eight F1progenies, including the reciprocals. All genotypes, including checks, were arranged in a Randomized Complete Block Design (RCBD) with three replications in the dry season of 2021/2022 and the rainy season of 2022 in Khon Kaen, Thailand. Genotype was significant for all observed traits, and the interaction between genotype and season was significant for all traits. The reciprocal cross-effect was non-significant for most observed traits. The non-significance of the interaction between N vs. R and season confirmed the absence of reciprocal cross effects in different growing seasons. Thus, dissecting one of two possibilities in each cross combination is advisable for affordable hybrid formations. Considering the absence of reciprocal cross effects but significant G × E effect for given traits, allocating more efforts and resources for conducting multi-environment trials is advisable to reduce the gap between actual and potential yields of testing hybrids.